Penggunaan Metode User Centered Design (UCD) dalam Perancangan Ulang Web Portal Jurusan Psikologi FISIP Universitas Brawijaya - Dini Pratiwi; Mochamad Chandra Saputra; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The role of website becomes the essential needs of organizations, including The Department of Psychology, Faculty of Social and Politic Sciences, University of Brawijaya. The department utilizes the website to inform about academic activities, announcements, etc. The development of website has come through usability guidelines to ensure that the goal of the website could be achieved. To produce user interface design which could be accepted by the users, it was used the approach of User Centered Design (UCD) which would involve the users in developing process. According to the first interview that has been conducted, The Department of Psychology's web has not been evaluated in a long time. Thus explain the students complained because they could not find the information they needed. The problems that contained in the initial design can be solved on the new design, but there are still constraints felt by the user. This research focused on how to give the recommendation in using the approach of UCD toward the problem which was resulted after doing the evaluation. This research discussed from initial design evaluation and the new design, problem analysis, understand and specify the context of use, specify user requirements, recommendation analysis, produce design solution, and final evaluation. The result of this research is the existing problems can be solved according to the design guidelines, which is listed in Standardization of UB and HHS guidelines.